Investigating the Effect of Power Intensity on Properties of Microwave Modified Oil Palm Trunk Lumber - Nurjannah Salim; Anis Izzati Ibrahim; Rasidi Roslan; Mohammad Ashry Jusoh; Rokiah Hashim (New Approaches in Engineering Research Vol. 5, 2021)
Oil palm tree (Elaeis guineensis) in Malaysia is one of the conventional plantations that is increasing year by year. Hence, the rate of oil palm biomass also increases in yet to come. Presently, oil palm biomass is going through research and development and appears to be the most sustainable alternative for the limitation of wood sources. Investigations on oil palm biomass have been conducted to support in draw out waste of oil palm and the meantime helping economic return to the country. This study was expected to estimate the effect of power intensity on the properties of microwave modified oil palm trunk lumber. Microwave treatment of oil palm trunk samples was set of connections by using a microwave operating at 2.45 GHz with the liberated process input power intensity (600-1000W). The impact and compression of the samples were tested. The analysis of properties of the fresh material and dry samples was employed using scanning electron microscopy (SEM) and thermal decomposition study using thermogravimetric analysis (TGA). The oven-drying samples were also conducted as a comparison of the conventional drying process in this research. Based on the outcomes of this study, microwave drying methods shows the effectiveness in the drying process